RNA interference in the red flour beetle Tribolium castaneum - Miller, Sherry C. (Kansas State University, 2009)
RNA interference (RNAi) is a natural gene-silencing phenomenon triggered by dsRNA (dsRNA). While RNAi is an endogenous process that plays essential roles in regulating gene expression it can also be harnessed as a tool for the study of gene function. Introducing dsRNA that is homologous to target mRNA into a cell triggers the RNAi response causing the destruction of the homologous mRNA and a loss of function phenotype. In some organisms, such as the nematode Caenorhabditis elegans, once dsRNA is introduced into the body cavity, the RNAi effect is seen throughout the organism because the dsRNA is taken up by individual cells and is then spread from cell to cell. This process has been termed the systemic RNAi response. For other organisms, such as the fruit fly Drosophila melanogaster, introduction of dsRNA into the body cavity does not result in a systemic RNAi response. This may be due to the cell’s inability to take up dsRNA or spread that dsRNA from cell to cell. For other organisms, including mammals, introduction of dsRNA into the body cavity does not result in a systemic RNAi response because the immune response causes dsRNA destruction before it can be utilized in the RNAi pathway. For organisms that do not exhibit a systemic RNAi response, complex genetic methods are needed to introduce dsRNA into cells to induce the RNAi response. Therefore, one of the challenges in utilizing RNAi as a genetic tool is introducing the dsRNA into individual cells. In recent years, systemic RNAi responses have been documented in both model and non-model organisms, making RNAi an accessible genetic tool. The red flour beetle, Tribolium castaneum is an emerging model organism that has a robust systemic RNAi response. However, the mechanism of systemic RNAi and the specific parameters required to obtain a strong systemic RNAi response in this organism have not been thoroughly investigated. The aim of this work is to provide data that can allow RNAi to be better utilized as a genetic tool in Tribolium and to use this information as a basis for the use of RNAi in other insects in which it can be performed. Specifically we provide data on the essential parameters necessary to achieve an effective systemic response in Tribolium, we describe differences in the systemic RNAi response between Drosophila and Tribolium, we analyze the conservation and function of RNAi machinery genes in Tribolium and we provide information on the genes critical for a systemic RNAi response in Tribolium.
Keywords: RNA interference; Tribolium castaneum; Red flour beetle; Double stranded RNA; Systemic; Drosophila melanogaster; Biology, Genetics (0369); Biology, Molecular (0307)